The Gargasian (Middle Aptian) of La Tuilière - St-Saturnin-lès-Apt (area of the Aptian historical stratotype, Vaucluse, SE France): geographic setting and outcrop correlation - Moullade Michel; Tronchetti Guy; Balme Christine; Kouyoumontzakis Georges (Carnets de Géologie, 2006)
A stratonomic and micropaleontological analysis of the Aptian marls cropping out in the La Tuilière area near Saint-Saturnin-lès-Apt (Vaucluse, SE France), enabled us to reconstitute a continuous succession almost 120 m thick, that includes the upper terms of the Lower Aptian (Bedoulian) and the lower part of the Middle Aptian (Gargasian). These levels had never before been observed with such continuity in the Gargas region, the Aptian historical stratotype.